Melatonin reduces LH, 17 beta-estradiol and induces differential regulation of sex steroid receptors in reproductive tissues during rat ovulation - Chuffa, Luiz Gustavo A. [UNESP]; Seiva, Fabio R. F. [UNESP]; Favaro, Wagner Jose [UNESP]; Teixeira, Giovana R. [UNESP]; Amorim, Joao P. A. [UNESP]; Mendes, Leonardo O. [UNESP]; Fioruci, Beatriz A. [UNESP]; Pinheiro, Patricia Fernanda F. [UNESP]; Fernandes, Ana Angelica H. [UNESP]; Franci, Janete A. A.; Delella, Flávia Karina [UNESP]; Martinez, Marcelo; et al. (Biomed Central Ltd., 2011)
Background: Melatonin is associated with direct or indirect actions upon female reproductive function. However, its effects on sex hormones and steroid receptors during ovulation are not clearly defined. This study aimed to verify whether exposure to long-term melatonin is able to cause reproductive hormonal disturbances as well as their role on sex steroid receptors in the rat ovary, oviduct and uterus during ovulation.Methods: Twenty-four adult Wistar rats, 60 days old (+/-250 g) were randomly divided into two groups. Control group (Co): received 0.9% NaCl 0.3 mL + 95% ethanol 0.04 mL as vehicle; Melatonin-treated group (MEL): received vehicle + melatonin [ 100 mu g/100 g BW/day] both intraperitoneally during 60 days. All animals were euthanized by decapitation during the morning estrus at 4 a. m.Results: Melatonin significantly reduced the plasma levels of LH and 17 beta-estradiol, while urinary 6-sulfatoximelatonin (STM) was increased at the morning estrus. In addition, melatonin promoted differential regulation of the estrogen receptor (ER), progesterone receptor (PR), androgen receptor (AR) and melatonin receptor (MTR) along the reproductive tissues. In ovary, melatonin induced a down-regulation of ER-alpha and PRB levels. Conversely, it was observed that PRA and MT1R were up-regulated. In oviduct, AR and ER-alpha levels were down-regulated, in contrast to high expression of both PRA and PRB. Finally, the ER-beta and PRB levels were down-regulated in uterus tissue and only MT1R was up-regulated.Conclusions: We suggest that melatonin partially suppress the hypothalamus-pituitary-ovarian axis, in addition, it induces differential regulation of sex steroid receptors in the ovary, oviduct and uterus during ovulation.